Implementasi Kebijakan Kurikulum Merdeka dalam Meningkatkan Keaktifan Belajar Siswa Sekolah Lanjutan Tingkat Pertama: Systematic Literature Review - Lalu M. Wiresentana; Winengan Winengan; Hadi Kusuma Ningrat (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: This study aims to analyze the implementation of the Merdeka Curriculum policy in enhancing student engagement in learning at the junior high school (SMP) level through a Systematic Literature Review (SLR) approach. The literature sources were obtained from scientific articles indexed in Scopus, DOAJ, and Google Scholar published within the last 10 years. The review process was conducted through the stages of identification, selection, evaluation, and synthesis of various research findings relevant to the implementation of the Merdeka Curriculum and student learning engagement. The research results indicate that the implementation of the Merdeka Curriculum has a positive impact on increasing student learning engagement through more flexible, contextual, and student-centered learning. This improvement is evident in student participation in discussions, collaboration skills, the courage to express opinions, and active involvement in project-based learning. However, the increase in student learning engagement has not occurred uniformly across all schools. The effectiveness of the Merdeka Curriculum’s implementation is influenced by teachers’ readiness, their ability to select learning strategies, support from school leadership, and the availability of learning facilities and infrastructure. Therefore, strengthening teachers’ competencies, institutional support, and continuous evaluation are necessary to optimize the implementation of the Merdeka Curriculum in improving the quality of learning at the junior high school level.Abstrak: Penelitian ini bertujuan untuk menganalisis implementasi kebijakan Kurikulum Merdeka dalam meningkatkan keaktifan belajar siswa Sekolah Menengah Pertama (SMP) melalui pendekatan Systematic Literature Review (SLR). Sumber literatur diperoleh dari artikel ilmiah yang terindeks Scopus, DOAJ, dan Google Scholar dengan rentang publikasi 10 tahun terakhir. Proses kajian dilakukan melalui tahap identifikasi, seleksi, evaluasi, dan sintesis terhadap berbagai hasil penelitian yang relevan dengan implementasi Kurikulum Merdeka dan keaktifan belajar siswa. Hasil penelitian menunjukkan bahwa implementasi Kurikulum Merdeka memberikan dampak positif terhadap peningkatan keaktifan belajar siswa melalui pembelajaran yang lebih fleksibel, kontekstual, dan berpusat pada siswa. Peningkatan tersebut terlihat dari partisipasi siswa dalam diskusi, kemampuan bekerja sama, keberanian menyampaikan pendapat, serta keterlibatan aktif dalam pembelajaran berbasis proyek. Namun demikian, peningkatan keaktifan belajar siswa belum terjadi secara merata pada seluruh sekolah. Efektivitas implementasi Kurikulum Merdeka dipengaruhi oleh kesiapan guru, kemampuan dalam memilih strategi pembelajaran, dukungan kepemimpinan sekolah, serta ketersediaan sarana dan prasarana pembelajaran. Oleh karena itu, diperlukan penguatan kompetensi guru, dukungan institusional, dan evaluasi berkelanjutan guna mengoptimalkan implementasi Kurikulum Merdeka dalam meningkatkan kualitas pembelajaran pada jenjang SMP.